Case Report: Massive Intestinal Pneumatosis and Pneumoretroperitoneum Following Hematopoietic Stem Cell Transplantation in a 2-Year-Old Child - Contini, Giorgia; Bertocchini, Arianna; Carta, Roberto; Merli, Pietro; Inserra, Alessandro; Bagolan, Pietro; Morini, Francesco (Frontiers in Pediatrics, 2021)
A 2-year-old boy with severe combined immunodeficiency (SCID) developed intestinal graft-versus-host disease (GVHD) after hematopoietic stem cell transplantation (HSCT), associated with massive intestinal pneumatosis (IP), pneumoretroperitoneum (PRP), and pneumomediastinum. His fair clinical conditions allowed conservative management, with progressive normalization of imaging findings. The patient did not require surgery and is alive and in good clinical conditions at follow-up. In children with GVHD-related IP but good clinical conditions and no signs of peritonitis, IP is not a mandatory indication for surgery, despite its potentially striking imaging features. Conservative management, with intestinal rest, decompression, and antibiotics, often allows regression of the clinical picture.